EDUCATIONAL MOBILITY AS A MEANS OF RETURN MIGRATION: YOUNG POLISH DIASPORA MEMBERS FROM THE FORMER USSR - Marcin Gońda (EtnoAntropoZum, 2018)
Poland has been traditionally a sending migration country. However, in recent years it receiv€es slowly growing number of return migrants. Among returnees arriving from the post-Soviet successor states the dominant group are youngsters who enroll for studies at Polish universities. The purpose of this autobiographical narrative interviews- based study is to present, firstly, the institutional conditions of conducting studies by Polish diaspora members. Particular attention is given to the latter’s arrivals as part of Poland’s return migration policy. Secondly, the article investigates biographical stories and aims at comparing two young Poles’ return paths to the ancestral homeland. It reconstructs their mobility stages in order to specify (1) relations between migration experience and transformation of their national identification and (2) impact of migration experience on their whole biography (biographical relevance). Since they stem from families of multi-ethnic background and relocate to a seemingly known place where only part of their predecessors come from, the concept of “roots migration” is utilised for the purpose of this study.